Beyond Recidivism: How Formerly Incarcerated Women Define Success. (February 2016) - Heidemann, Gretchen; Cederbaum, Julie A.; Martinez, Sidney
This study explores how formerly incarcerated women define success. Qualitative analysis of data from in-depth interviews with 30 women who had been released from prison at least 3 months prior to the interview suggests that avoiding recidivism is only one aspect of success for this population. Success is defined as having their own place, helping family members and others, living free from criminal justice surveillance, persevering through challenges, and living a "normal life." Ways in which these conceptualizations expand traditional notions of success for this population are discussed. Limitations and suggestions for future research are offered.